LncRNAs in Stem Cells - Shanshan Hu; Ge Shan (Hindawi Limited, 2016)
Noncoding RNAs are critical regulatory factors in essentially all forms of life. Stem cells occupy a special position in cell biology and Biomedicine, and emerging results show that multiple ncRNAs play essential roles in stem cells. We discuss some of the known ncRNAs in stem cells such as embryonic stem cells, induced pluripotent stem cells, mesenchymal stem cells, adult stem cells, and cancer stem cells with a focus on long ncRNAs. Roles and functional mechanisms of these lncRNAs are summarized, and insights into current and future studies are presented.